Respostas
respondido por:
3
Olá!!!
Resolução!!
Função :
f ( x ) = mx + p
• f ( 1 ) = 6 → m • 1 + p = 6 → m + p = 6
• f ( - 1 ) = 4 → m • ( - 1 ) + p = 4 → - m + p = 4
Sistema :
{ m + p = 6
{ - m + p = 4
——————— +
0 + 2p = 10
2p = 10
p = 10/2
p = 5
m + p = 6
m + 5 = 6
m = 6 - 5
m = 1
Logo, m = 1, e p = 5
Espero ter ajudado!!
Resolução!!
Função :
f ( x ) = mx + p
• f ( 1 ) = 6 → m • 1 + p = 6 → m + p = 6
• f ( - 1 ) = 4 → m • ( - 1 ) + p = 4 → - m + p = 4
Sistema :
{ m + p = 6
{ - m + p = 4
——————— +
0 + 2p = 10
2p = 10
p = 10/2
p = 5
m + p = 6
m + 5 = 6
m = 6 - 5
m = 1
Logo, m = 1, e p = 5
Espero ter ajudado!!
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás